PELATIHAN PENYUSUNAN MATERI AJAR MENGGUNAKAN APLIKASI GAMMA BAGI CALON GURU BAHASA INDONESIA - Simanjuntak, Dairi Sapta Rindu; Mubarak, Zia Hisni; Rudianto, Gaguk; Wulan , Eka Putri Saptari; Johan , Mhd.; Pangaribuan, Jontra Jusat (ASOSIASI IDEBAHASA KEPRI, 2025)
The training program on Developing Teaching Materials Using the Gamma Application for Indonesian Language Teacher Candidates was conducted with the primary aim of enhancing the participants' competencies in utilizing technology for educational purposes. This initiative involved 30 participants from various universities in Medan, yielding significant improvements in their knowledge and skills. Prior to the training, only about 30% of participants felt confident in using the Gamma application; however, this figure rose to 85% post-training. Participants successfully created creative digital teaching materials that aligned with curriculum standards, incorporating engaging multimedia elements. In addition to technical skill enhancement, the training also boosted participants' motivation to learn, making the material development process more enjoyable. Despite challenges related to varying technological abilities and limited internet access, effective mentoring strategies and the provision of independent learning resources proved beneficial. The outcomes of this training are expected to positively impact the quality of education in Indonesia and inspire similar initiatives in the future.